2007
DOI: 10.1097/id.0b013e318065a84c
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Comparison of Light Emitting Diode Phototherapy-Treated Hydroxyapatite-Grafted Extraction Sockets: A Same-Mouth Case Study

Abstract: The accelerated bone healing in the phototherapy-treated HA socket graft may provide faster implant placement compared to non-phototherapy-treated socket grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
13
1
1
Order By: Relevance
“…19,43 OsseoPulse ® LED device photobiomodulation was found to enhance bone formation and particle resorption in HA particulate-grafted fresh extraction sockets. 44 In another study by OsseoPulse ® LED device, a favorable effect on healing and stability of 12 titanium orthodontic miniscrews was reported. 45 The results of our study and those of others indicated that bone irradiated with LED arrays showed increased neovascularization, collagen deposition, and bone neorformation compared to non-irradiated bone.…”
Section: Discussionsupporting
confidence: 74%
“…19,43 OsseoPulse ® LED device photobiomodulation was found to enhance bone formation and particle resorption in HA particulate-grafted fresh extraction sockets. 44 In another study by OsseoPulse ® LED device, a favorable effect on healing and stability of 12 titanium orthodontic miniscrews was reported. 45 The results of our study and those of others indicated that bone irradiated with LED arrays showed increased neovascularization, collagen deposition, and bone neorformation compared to non-irradiated bone.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have suggested that the use of PBM is one of the most suitable protocols for improving bone repair due to its larger penetration depth in the bone tissue when compared to visible light [19]. Although several studies have demonstrated positive results in the healing of bone tissue with the use of PBM, there are yet few reports on the use of combinations of PBM and biomaterials [20,21]. The effects of PBM in bone repair associated with graft biomaterials needs to be further studied as each material may cause different responses.…”
Section: Introductionmentioning
confidence: 99%
“…As light has been proved to speed up bone repair, it would be desirable to develop a technique to enhance and shorten the time of bone repair in cases of the use of biomaterials [20]. The aim of this study was to histopathologically evaluate the effect of PBM and locally applied simvastatin on bone formation in 5 mm critical sized defects (CSDs) formed in rat calvaria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this stimulation of the respiratory chain in the mitochondria, adenosine triphosphate (ATP) production is increased [16]. It is postulated that this increased ATP production and consequent energy source for the cellular machinery allows for increased function and metabolism of cells in tissues that are ischemic, wounded, intoxicated, or poorly perfused [17].…”
Section: Introductionmentioning
confidence: 99%